Preoperative mechanical bowel preparation in elective colorectal surgery: an update of systematic review of the literature and meta-analysis - Güenaga,Katia Ferreira (2012)
The belief that mechanical bowel preparation is related to the reduction of complications in elective colorectal surgery is based on observational studies and expert opinion. This question led the authors to a systematic literature review, with the completion of meta-analysis, followed by three updates. METHOD: The sources of information were EMBASE, LILACS, MEDLINE, IBECS, the Cochrane Controlled Trials Register and letters to the authors. The studies were included according to the randomization criteria. The studied variables were: anastomotic dehiscence, mortality and operatory wound infection. The analysis was divided into two comparisons: one group with mechanical preparation (Group A) compared with a group without preparation (Group B) (Comparison I) and a group submitted to rectal enema (Comparison II). RESULTS: We analyzed 5,805 patients in 20 clinical trials. In comparison I, anastomotic leak occurred in 4.4% (101/2,275 patients) in Group A and 4.5% (103/2,258 patients) in Group B. In comparison II, anastomotic leak occurred in 4.4% (27/601 patients) in Group A and 3.4% (21/609 patients) in Group B. CONCLUSION: Despite the inclusion of more studies, evidences found in studies did not show any benefit obtained from the use of preoperative mechanical bowel preparation or rectal cleansing enemas in elective colorectal surgery.